2018
DOI: 10.1007/s00300-018-2411-5
|View full text |Cite|
|
Sign up to set email alerts
|

Summer phyto- and bacterioplankton communities during low and high productivity scenarios in the Western Antarctic Peninsula

Abstract: Phytoplankton blooms taking place during the warm season drive high productivity in Antarctic coastal seawaters. Important temporal and spatial variations exist in productivity patterns, indicating local constraints influencing the phototrophic community. Surface water in Chile Bay (Greenwich Island, South Shetlands) is influenced by freshwater from the melting of sea ice and surrounding glaciers, however it is not a widely studied system. The phyto-and bacterioplankton communities in Chile Bay were studied ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…Total DNA and RNA were obtained from the 0.22 μm filters collected on February 14th and March 4th, which represent samples collected at low and high Chl- a content periods (L-C and H-C), respectively as described in Alcamán-Arias et al (2018) and Fuentes et al (2018). DNA and RNA extractions were performed with the method of Díez et al (2001), as described in Alcamán-Arias et al (2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total DNA and RNA were obtained from the 0.22 μm filters collected on February 14th and March 4th, which represent samples collected at low and high Chl- a content periods (L-C and H-C), respectively as described in Alcamán-Arias et al (2018) and Fuentes et al (2018). DNA and RNA extractions were performed with the method of Díez et al (2001), as described in Alcamán-Arias et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 16S rRNA gene sequences present in the metagenomes were identified and extracted using Ribopicker (Schmieder et al, 2012), then annotated using Blastn (Camacho et al, 2009) with Silva 123 SSU database (Quast et al, 2013) and displayed with MEGAN 6 (Huson et al, 2016). For the photosynthetic eukaryotic community composition, sequences matching chloroplast 16S rRNAs from 20–8 to 8–0.22 μm filter fractions sequenced with Illumina TAGs (iTAGs) from the study of Fuentes et al (2018) were extracted, combined and reassigned against Phytoref database (Decelle et al, 2015), and analyzed for their relative abundance and composition. The activity of the phytoplankton community was assessed with total transcripts as well as metabolic genes such as rubisco (rbcL) and photosystem a (psbA) as described in Alcamán-Arias et al (2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreno-Pino et al (2016) also found that in surface waters around the South Shetland Islands, the environmental filtering effect had a significant impact on the composition of the phytoplankton communities. Based on data collected at different sites in Chile Bay (Greenwich Island, South Shetlands) during the spring bloom, it was postulated that autotrophic organisms were affected by preceding blooms during spring (Alcamán-Arias et al 2018;Fuentes et al 2019). Diatoms, especially Thalassiosirales, were the most abundant phytoplankton group in this period.…”
Section: Antarctic Diversity and Ecologymentioning
confidence: 99%
“…Investigations conducted by using high-throughput sequencing on 18S rRNA gene of planktonic microbial eukaryote community in Arctic Ocean (a) and Southern Ocean (b)(Bachy et al 2011;Balzano et al 2012;Comeau et al 2011;Fuentes et al 2019;Hyoung et al …”
mentioning
confidence: 99%